High-entropy (HfTaTiNbZr)C and (HfTaTiNbMo)C carbides fabricated through reactive high-energy ball milling and spark plasma sintering. Issue 11 (1st August 2020) - Moskovskikh, D.O.; Vorotilo, S.; Sedegov, A.S.; Kuskov, K.V.; Bardasova, K.V.; Kiryukhantsev‐korneev, Ph.V.; Zhukovskyi, M.; Mukasyan, A.S.
Abstract: Powders of high-entropy Hf0.2 Ta0.2 Ti0.2 Nb0.2 Zr0.2 C (HECZr ) and Hf0.2 Ta0.2 Ti0.2 Nb0.2 Mo0.2 C (HECMo ) carbides were fabricated through the reactive high-energy ball milling (R-HEBM) of metal and graphite particles. It was found that 60 min of R-HEBM is adequate to achieve a full conversion of the initial precursors into a FCC solid solution for both compositions. The HECZr powder possesses a unimodal particle size distribution (40% d ≤ 1 μm, 95% d ≤ 10 μm), and the HECMo powder features a bimodal distribution with a slightly larger particle size overall (30% d ≤ 1 μm, 80% d ≤ 10 μm). Bulk high-entropy ceramics with a minor presence of an oxide phase were fabricated through the spark plasma sintering of these high-entropy powders at 2000 °C with a 10 min dwelling time. The HECZr ceramics possess a relative density of up to 94.8%, hardness of 25.7 ± 3.5 GPa, Young's modulus of 473 ± 37 GPa, and thermal conductivity of 5.6 ± 0.1 W/m·K. HECMo ceramics with a relative density of up to 93.8%, hardness of 23.8 ± 2.7 GPa, Young's modulus of 544 ± 48 GPa, and thermal conductivity of 5.9 ± 0.2 W/m·K were also fabricated. A comparison of the properties of the HECs produced in this study and those previously reported is also provided.